Phosphine‐Catalyzed Synthesis of Chiral N‐Heterocycles through (Asymmetric) P(III)/P(V) Redox Cycling. Issue 22 (15th June 2021) - Lorton, Charlotte; Saleh, Nidal; Voituriez, Arnaud
Abstract: Phosphine‐catalyzed tandem Michael addition/intramolecular Wittig reactions have been developed for the synthesis of chiral 2, 5‐dihydro‐1 H ‐pyrrole and tetrahydropyridine derivatives. These processes have been rendered catalytic in phosphine, thanks to the in situ reduction of phosphine oxide by phenylsilane. Furthermore, catalytic and asymmetric P(III)/P(V) processes were implemented using enantiopure chiral phosphines. Abstract : An access to chiral 2, 5‐dihydro‐1 H ‐pyrroles and tetrahydropyridines has been elaborated through a phosphine‐catalyzed Michael addition/Wittig reaction. The use of catalytic amounts of chiral phosphines affords these nitrogen heterocycles with promising enantioselectivities.